Knowledge and assertion : a critique of Lackey - Anderson, Joshua (Array, 2020)
In the literature on assertion, there is a common assumption that having the knowledge that p is a sufficient condition for having the epistemic right to assert that p—call this the Knowledge is Sufficient for Assertion Principle, or KSA. Jennifer Lackey has challenged KSA based on several counterexamples that all, roughly, involve isolated secondhand knowledge. In this article, I argue that Lackey’s counterexamples fail to be convincing because her intuition that the agent in her counterexamples both has knowledge and do not have the epistemic right to assert is wrong. The article will progress as follows: In section 2, I present Lackey’s argument. In section 3, I suggest some more general reasons for doubting that the agent in her counterexamples actually has knowledge. I then show that from a virtue theoretic and Edward Craig’s practical explication of knowledge perspectives the agent in Lackey’ s counterexamples does not know. Since the agent in Lackey’s counterexamples does not have knowledge, she has failed to convincingly prove that KSA is false. In section 4, I conclude by suggesting that, at most, what Lackey’s counterexamples demonstrate is a problem with a simplistic evidentialist and/or process reliabilist epistemology.